The Effect Of The Imperative Method On The Learning Process Of The Passing Skill In Handball Among Students In The First Year Of Secondary School - Zemali, Mohamed; benyoucef, dahou; derbal, fethi (sports creativity, 2025)
The research aims to determine the impact of the imperative style on the process of learning the passing skill in handball among students in the first year of secondary school, the study was conducted on 08 female students who were randomly selected using the experimental method. The results of the research led to the fulfilment of the proposed hypothesis. We recommend the necessity of adopting the process of learning the skill of passing in handball for students in the first year of secondary schoo